The Correlation Between Folic Acid Supplementation And Change In Cognitive Function In Elderly (A Study of The Effect of Folic Acid Supplementation on Homocysteine Levels) - Adinda Putri Larastiti; Hexanto Muhartomo; Amin Husni; Endang Kustiowati; Herlina Suryawati; Arinta Puspita Wati (Medica Hospitalia : Journal of Clinical Medicine, 2025)
Background: A good cognitive function is one of the things that affect the quality of life of the elderly. Decreased cognitive function in elderly can be caused by physiological or pathological processes. Increased homocysteine is one of risk factors associated with decreased cognitive function. Folic acid supplementation has been shown to reduce homocysteine levels. The aim: To know the relationship between folic acid supplementation and change in cognitive function in elderly. Methods: This research is a quasi-experimental study at Pucang Gading Nursing Home, Semarang. A total of 30 subjects were divided into 2 groups, namely 15 treatment subjects (given folic acid supplementation 1 mg/24 hours) and 15 control group subjects (given placebo), 1 subject dropped out due to death. The study was conducted for 12 weeks, assessment of homocysteine level and cognitive function (with MoCA Ina) was carried out before and after the study. Results: There was no relationship between folic acid supplementation and changes in homocysteine level (p 0.322). There is a relationship between folic acid supplementation with change in cognitive function in elderly (p 0.000). There is a relationship between changes in homocysteine level and  global change in cognitive function in elederly (p 0.018), Conclusion: There is a significant relationship between folic acid supplementation and change in cognitive function in elderly.